2021
DOI: 10.3390/nano11020327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrolyte on Laser-Induced Periodic Surface Structures with Picosecond Laser Pulses

Abstract: Short-pulsed laser-induced periodic surface structures (SPLIPSSs) have the possibility to control tribology, wettability and biocompatibility. Nevertheless, the optimal structure depends on each functionality, which has not been clarified. The hybrid process with a short-pulsed laser and electrochemical machining (SPLECM) is, then, proposed to fabricate micro/nano hybrid structures and to modify the surface composition for providing high functionalities with material surfaces. Electrochemical machining is a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Much work has been conducted on the effect of the laser parameters on the period of LSFLs. It was concluded that laser wavelength [17,18] had the main responsibility for the period of LSFLs and laser power [19,20], angle of incidence [21], and scan speed [20,22], slightly modifying the period of LSFLs. As a result, the period of LSFLs can be easily modified by regulating the laser wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been conducted on the effect of the laser parameters on the period of LSFLs. It was concluded that laser wavelength [17,18] had the main responsibility for the period of LSFLs and laser power [19,20], angle of incidence [21], and scan speed [20,22], slightly modifying the period of LSFLs. As a result, the period of LSFLs can be easily modified by regulating the laser wavelength.…”
Section: Introductionmentioning
confidence: 99%